Slope Stability Analysis in the Terrace Area of ​​Sentul City, Bogor Regency - Lukman, Hikmad (Journal of Science Innovare, 2024)
The landscape in the Terrace Hill Sentul City area of Bogor Regency is at level + 280 to + 307 above sea level. is a contoured area, planned to be used as a housing area with a Down Hill and Up Hill model. For this reason, it is necessary to carry out land preparation in the form of Excavation (Cutting) and Fill work, while because the condition of the sloping land and the type of soil in the form of silt has the potential to experience landslides, for this reason, slope reinforcement work is needed. This area also borders a residential area so that an evaluation needs to be carried out whether the land preparation work does not interfere with the area owned by local residents. Based on the results of calculations and analysis of slope stability using the Splicing method and the Plaxis program, it was obtained that in the Terrace Hill area, slope stability engineering needs to be carried out. Handling of this housing area can use the construction of retaining walls from stone or concrete cyclops, placement of piles of sacks filled with soil, installation of gabions or using bamboo cerucuk, dolken and bored pile poles